2017
DOI: 10.1108/ijebr-07-2016-0213
|View full text |Cite
|
Sign up to set email alerts
|

The trinity of entrepreneurial team dynamics: cognition, conflicts and cohesion

Abstract: Purpose Cognition, conflict and cohesion constitute an inseparable body of group dynamics in entrepreneurial teams. There have been few studies of how entrepreneurial team members interact with each other to enhance venture performance. The purpose of this paper is to develop and test a model that explains the trinity of cognition, conflict and cohesion in terms of social interaction between entrepreneurial team members. Design/methodology/approach Drawing upon the existing literature concerning entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 56 publications
(116 reference statements)
1
46
0
3
Order By: Relevance
“…Venture performance is the goal behind the establishment and development of entrepreneurial companies, and is also a focal point of discussion in the entrepreneurial research field [7,19]. Scholars believe that the impact on the behavior of the entrepreneur mainly manifests itself in the form of venture performance [16]. Furthermore, venture performance is not just the enumeration of various related indicators, but rather a more systematic whole that should yield related indicators through the analysis of the environment of the company, the entrepreneurial team, and the individuals composing that team [20].…”
Section: Venture Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Venture performance is the goal behind the establishment and development of entrepreneurial companies, and is also a focal point of discussion in the entrepreneurial research field [7,19]. Scholars believe that the impact on the behavior of the entrepreneur mainly manifests itself in the form of venture performance [16]. Furthermore, venture performance is not just the enumeration of various related indicators, but rather a more systematic whole that should yield related indicators through the analysis of the environment of the company, the entrepreneurial team, and the individuals composing that team [20].…”
Section: Venture Performancementioning
confidence: 99%
“…Meanwhile, current research on the relationship between entrepreneurial teams and venture performance has focused on the internal mechanism of the structure and characteristics of entrepreneurial teams (e.g., heterogeneity, knowledge sharing, conflict resolution, and innovation ability) affecting venture performance, while the theoretical regulation behind the effect of entrepreneurial team characteristics on venture performance is yet to be interpreted [15]. In this case, team cognition theory is introduced to this study, wherein entrepreneurial team characteristics are divided into cognition characteristics and behavior characteristics, and the chain of "cognition-behavioroutcome" is followed to analyze the relationship between entrepreneurial team characteristics and venture performance [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the fit of such topics with the call for papers, unfortunately the studies came short in terms of adequate grounding into the existing body of work. For example, conflict in entrepreneurial teams (Breugst, Patzelt, & Rathgeber, 2015;Chen, Chang, & Chang, 2017) or their methodology was not rigorous enough in terms of research design, data collection, or data analysis.…”
mentioning
confidence: 99%
“…Even though scholars have given growing attention to topics of conflict management and negotiation in family firms (Caputo & Zarone, 2019;Caputo et al, 2018b;Kellermanns & Eddleston, 2007) and in entrepreneurial teams (Breugst et al, 2015;Chen et al, 2017), the analysis of how entrepreneurs negotiate and how conflict impacts entrepreneurial ventures and SMEs as opposed to larger businesses still has many topics to investigate.…”
mentioning
confidence: 99%
“…For example, scholars have demonstrated that factors such as cognitive style (Adomako et al, 2016), values (Kirkley, 2016) and team interactions (Chen et al, 2017) significantly influence entrepreneurial efforts. In spite of this, extant entrepreneurship research on the cognitions, attitudes and behaviors of entrepreneurs can be characterized as holding significant untapped potential to provide transformative insights regarding these important economic actors.…”
Section: Introductionmentioning
confidence: 99%